(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The study aimed determine what is the image of Adonara Women in Lamaholot culture in Bara Pattyradja’s poetry and what are the culture values contained in Bara Pattyradja’s poetry. This study method was used descriptive qualitative, which describe about the image of Adonara Women in Lamaholot culture in Bara Pattyradja’s poetry and to find out the culture values contained in Bara Pattyradja’s poetry. The result of this study is that the Bara Pattyradja poetry is a cultural reflection on the culture of the Lamaholot tribe. How the image of women and cultural values is describe by the poet in this poetry through representations of daily life, hereditary habits, and customs of the Adonara community.